WAYS TO IMPROVE ENGLISH READING SKILLS OF FUTURE CHEMICAL ENGINEERS - Shokirova Mukaddas Musakhonovna (Research Focus International Scientific Journal, 2025)
In this article it is discussed current issues of language skills development in future chemical engineers. It is identified the main problems and difficulties that students face when learning English in the context of a technical specialty based on the analysis of scientific literature and the results of an empirical study. Innovative approaches to teaching aimed at developing communicative competence, developing the skills of reading scientific literature and conducting a professional discussion in English are proposed.